A mixed methods exploration of the romantic relationship experiences for the transgender population and their partners - Marshall, Ellen Louise (2022)
Introduction: Transgender individuals face many challenges with their lives and may experience poorer mental health and lower quality of life compared to cisgender individuals. Social support is a key variable to improve wellbeing and ensure positive gender affirming medical treatment and transition outcomes. However, many transgender individuals report low levels of perceived social support and interpersonal difficulties. Within the general population, satisfying relationships are associated with good mental health and wellbeing, however there is a current lack of understanding and support for transgender relationships. Additionally, there is a lack of understanding of the partner experience meaning both their role as a supporter and the impact of transition on their own mental health and wellbeing remains unknown.